2009
DOI: 10.1364/ol.34.003565
|View full text |Cite
|
Sign up to set email alerts
|

Broadband conversion of visible light to near-infrared emission by Ce^3+, Yb^3+-codoped yttrium aluminum garnet

Abstract: We show that Ce(3+) can be an efficient sensitizer for Yb(3+) in the host lattice of yttrium aluminum garnet (YAG). With blue-light excitation to induce the 4f-->5d transition of Ce(3+), characteristic near-IR emission of Yb(3+) due to transition of (2)F(5/2)-->(2)F(7/2) peaking at 1030 nm is generated as a result of energy transfer from Ce(3+) to Yb(3+). The result of spectral evolution with temperature indicates that the efficiency of energy transfer is enhanced owing to thermal effect. This evidence implies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(77 citation statements)
references
References 7 publications
6
70
0
1
Order By: Relevance
“…It can be seen from Fig. 1 that the addition of Ce 3+ ions into the glass matrix results in a red-shift of the UV-side absorption edge, and this is assigned to the 4f → 5d transition in Ce 3+ ions which causes a broad absorption around 400-500 nm [20][21][22].…”
Section: Methodsmentioning
confidence: 96%
“…It can be seen from Fig. 1 that the addition of Ce 3+ ions into the glass matrix results in a red-shift of the UV-side absorption edge, and this is assigned to the 4f → 5d transition in Ce 3+ ions which causes a broad absorption around 400-500 nm [20][21][22].…”
Section: Methodsmentioning
confidence: 96%
“…The long lifetime is about the same in the G and GC48 ( $1-1.4 ms). The average luminescence lifetime can be derived from the following equation [43]:…”
Section: Photoluminescencementioning
confidence: 99%
“…7. Generally speaking, the 5d 2 ( 2 B 1g ) energy state could relax to lower 5d 1 ( 2 A 1g ) level easily and then transmitted to 2 F 5/2 rapidly [14,21]. Based on the analysis, the energy transfer between Ce 3+ and Nd 3+ was presumed as follow:…”
Section: Energy Transfer Mechanismmentioning
confidence: 99%
“…5d transition lies in a broad spectral range and the energy of the transition changes with different crystal field strength of the matrix. Recent studies have demonstrated that Ce 3+ -doped YAG matrix has a strong and broad absorption from 350 nm to 550 nm accordance with the strongest emission of solar spectrum [21,22], furthermore, the 5d 1 ( 2 A 1g ) level of Ce 3+ is as twice as the 4 F 3/2 ! 4 I 11/2 transition of Nd 3+ , which is possible to realize efficiency DC.…”
Section: Introductionmentioning
confidence: 99%